Periodontitis as a possible early sign of diabetes mellitus - Teeuw, Wijnand J (BMJ Open Diabetes Res Care, 2017)
OBJECTIVE: The early diagnosis of (pre)diabetes mellitus is essential for the prevention of diabetes complications. It has been suggested that gum disease (periodontitis) might be an early complication of diabetes and may be a useful risk indicator for diabetes screening. Therefore, a dental office could be a good location for screening for (pre)diabetes in patients with periodontitis using a validated glycated hemoglobin (HbA1c) dry spot analysis. RESEARCH DESIGN AND METHODS: A total of 313 individuals from a university dental clinic participated. From 126 patients with mild/moderate periodontitis, 78 patients with severe periodontitis and 109 subjects without periodontitis, HbA1c values were obtained by the analysis of dry blood spots. Differences in mean HbA1c values and the prevalence of (pre)diabetes between the groups were analyzed. RESULTS: The mild/moderate and severe periodontitis groups showed significantly higher HbA1c values (6.1%±1.4% (43 mmol/mol±15 mmol/mol) and 6.3%±1.3% (45 mmol/mol±15 mmol/mol), respectively) compared with the control group (5.7%±0.7% (39 mmol/mol±8 mmol/mol), p=0.003). In addition, according to the American Diabetes Association (ADA) guidelines for diagnosis, there was a significant over-representation of subjects with suspected diabetes (23% and 14%) and pre-diabetes (47% and 46%) in the severe periodontitis group and mild/moderate periodontitis groups, respectively, compared with the control group (10% and 37%, p=0.010). Notably, 18.1% of patients with suspected new diabetes were found among subjects with severe periodontitis compared with 9.9% and 8.5% among subjects with mild/moderate periodontitis and controls, respectively (p=0.024). CONCLUSIONS: The dental office, with particular focus on patients with severe periodontitis, proved to be a suitable location for screening for (pre)diabetes; a considerable number of suspected new diabetes cases were identified. The early diagnosis and treatment of (pre)diabetes help to prevent more severe complications and benefit the treatment of periodontitis.